An Analysis of Transitivity in Analytical Exposition Texts Written by Eleventh Grade Students - Nur Septianti, Yulia; Kurniawan, Eri (LETS: Journal of Linguistics and English Teaching Studies, 2023)
While studies on ideational metafunctions have been widely reported, research on transitivity analysis on students’ analytical exposition texts in EFL contexts is under-explored. The aims of this study are twofold: scrutinizing the process types and investigating the most dominant process in analytical exposition text as guided by Systemic Functional Linguistics theory. This study applied descriptive qualitative design focusing on experiential metafunction, comprising the processes of material, mental, verbal, relational, behavioral, and existential. The results show that among the six processes, the material process had the highest frequency of occurrence (45.6%), followed by the processes of relational (43.6%), mental (6.8%), verbal (1.94%), and finally, existential (1.94%). To conclude, the linguistic features of analytical exposition text, which is mental processes, are not accurately employed in the texts.  The pedagogical implications of this study are: 1) encouraging students to study analytical exposition text and 2) helping students to think critically. Based on the findings, we suggest that the teacher is required to teach the text explicitly. In this context, explicit teaching can be done using a genre-based approach. Therefore, the students can comprehend the analytical exposition text as a whole.